2008
DOI: 10.1007/s10751-008-9846-y
|View full text |Cite
|
Sign up to set email alerts
|

Iron speciation in fault gouge from the Ushikubi fault zone central Japan

Abstract: Chemical species of iron and sulfur were measured using 57 Fe Mössbauer spectroscopy and X-ray near edge structure, respectively, for the fault gouge samples collected from two sites along the ENE-WSW trending Ushikubi fault zone in central Japan. These gouge samples have distinguishable variations in their physical properties such as surface color and structure and these features are also reflected by the chemical speciation of iron and sulfur. Newly formed minerals, including calcite, dolomite, siderite, iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the deep part of an active fault, there are often reducing fluids migrating up the fault, which leads to the reduction of iron in the shallow fault gouge. The Ushikubi fault zone in central Japan illustrated ferric oxide and reduced iron in the old and new faults, respectively , indicating these redox shifts probably relate to the material exchange between the fault gouge and the external or deep [42]. Ma Xiangxian studied the iron species of fresh fault gouge in Wenchuan fault zone which had an 8.0 earthquake magnitude in 2008 and found that the fault gouge is mainly enriched with reduced Fe, it is resulted from exchange with deep reducing materials and suggest it a typical active fault [43].…”
Section: Fe Speciesmentioning
confidence: 99%
“…In the deep part of an active fault, there are often reducing fluids migrating up the fault, which leads to the reduction of iron in the shallow fault gouge. The Ushikubi fault zone in central Japan illustrated ferric oxide and reduced iron in the old and new faults, respectively , indicating these redox shifts probably relate to the material exchange between the fault gouge and the external or deep [42]. Ma Xiangxian studied the iron species of fresh fault gouge in Wenchuan fault zone which had an 8.0 earthquake magnitude in 2008 and found that the fault gouge is mainly enriched with reduced Fe, it is resulted from exchange with deep reducing materials and suggest it a typical active fault [43].…”
Section: Fe Speciesmentioning
confidence: 99%
“…Accordingly, lower amounts of gas could be absorbed in the nearby gouge. As the distance from the fault plane increases, so does the clay content in the fault gouge, which may indicate a self-sealing by fine particles within the fault zone (Zheng et al, 2008) and a stronger adsorptive capacity to trap much more gas. The absorbed gas concentrations in this study are likely lowered dramatically at the cataclasite zone because of these changes in porosity and fracture structures.…”
Section: Absorbed Gas Variation Trend In the Vertical Profilementioning
confidence: 99%
“…Some of these investigations include: the use of iron speciation [12], the use of geomorphology and geology [13, 14], and the use of the radiocarbon dating method [15–17]. Although the age of the latest event of the Ushikubi fault has been estimated indirectly using the radiocarbon dating method, the ESR method has not yet been employed.…”
Section: Introductionmentioning
confidence: 99%